Critical Reading Development Based On Buddhadhamma’s Thinking Methods - Summart, Marin (Ph.D. in Social Sciences Journal, 2022)
This academic article aim to analyze as follows: (1) to study and analyze the theories of reading and thinking processes (2) to study and analyze the theories of critical reading (3) to study and analyze the Teachings of Buddhadhamma on thinking processes (4) to study and analyze the Thinking Methods of Yonisomanasikarn for critical reading skill development. Literature reviews have been divided into four items: (1) the theories of reading and thinking processes (2) the theories of critical reading (3) the Teachings of Buddhadhamma on thinking processes. The study found that (1) Reading and thinking process cannot be separated definitely, they have close relationship. The reader must think while they are reading. (2) In critical reading, the readers have to apply their memory, understanding, interpreting, evaluating, criticizing and creating to get the main idea and the objectives that the writers communicate in their writing. (3) the Teachings of Buddhadhamma on thinking processes emphasize on right method thinking solve the problems of daily livings for the better quality of lives. (4) Yonisomanasikarn is reading skill development the Buddhism method of right thinking which plays a very important role in determining a personality and good practical way of living. Yonisomanasikarn is valuable and effective method of thinking in critical reading skill development.